Pembuat Keputusan Kepala Sekolah - Yuri, Yuriansyah; Riswandi, Riswandi (JURNAL MANAJEMEN MUTU PENDIDIKAN, 2023)
Abstract: Principal Decision Maker. Decision making is important in determining policy or a problem. there are times when the principal is well received by the teacher, there are times when he is not. The principal's decision is well received, marked by support for the decision and the responsibility of teachers and staff in carrying out the decisions made. Acceptance of a decision is very dependent on the readiness and ability of the teacher and staff as the implementer of the decision. Of course, before making a decision, we must know the style of decision and the stages before making a decision. The method used to write this article is literature review, which first collects research papers that are relevant to decision making in the form of books, journals obtained from Google Scholar, and other sources. The principal's decision-making points to ideas that can solve problems in ways that make it more acceptable to all parties. First, the problem must be well known and formulated, while the solution must be based on selecting the best alternative among existing alternatives. Decision making in the implementation process must pay attention to the effectiveness of the decision making, so that there is compatibility between the problems faced and the solutions to the problems taken.Keywords: Decision-making, Leadership, PrincipalsDOI: 10.23960/jmmp .v11.i1.2023.01